Critical Indicators for Improving Compliance of Fuel Trading Business Entities in Indonesia - Husniyadi, Ilham; Moeis, Armand Omar (Department Industrial Engineering, University of Muhammadiyah Malang, 2024)
Fuel oil is one of Indonesia's most dominant types of energy, making it important to have strict oversight and regulation of its supply and distribution. This research aims to identify compliance indicators for fuel trading business entities in the downstream oil and gas sector and develop guidelines to monitor and improve the level of compliance of these entities. The method used in this research is the Analytical Hierarchy Process (AHP). The results showed ten relevant compliance indicators: waste management, resource use, occupational accident rate, safety training, audits and inspections, regulatory violations, social and community contributions, stakeholder satisfaction, operational efficiency, and tax and financial compliance. Of the ten indicators, the highest weight is obtained from regulatory violations at 42%, followed by the work accident rate at 22%. These findings provide a strong basis for monitoring and improving compliance in the oil and gas trading business and supporting better and sustainable energy management in Indonesia.